Evaluation of an Intravitreal Rho-Associated Kinase Inhibitor Depot Formulation in a Rat Model of Diabetic Retinopathy - Cecile Lebon; Heike Neubauer; Marianne Berdugo; Kimberley Delaunay; Elke Markert; Kolja Becker; Katja S. Baum-Kroker; Jürgen Prestle; Holger Fuchs; Remko A. Bakker; Francine Behar-Cohen (MDPI AG, 2021)
Rho-associated kinase (ROCK) activation was shown to contribute to microvascular closure, retinal hypoxia, and to retinal pigment epithelium (RPE) barrier disruption in a rat model of diabetic retinopathy. Fasudil, a clinically approved ROCK inhibitor, improved retinal perfusion and reduced edema in this model, indicating that ROCK inhibition could be a promising new therapeutic approach for the treatment of diabetic retinopathy. However, due to its short intravitreal half-life, fasudil is not suitable for long-term treatment. In this study, we evaluated a very potent ROCK1/2 inhibitor (BIRKI) in a depot formulation administered as a single intravitreal injection providing a slow release for at least four weeks. Following BIRKI intravitreal injection in old Goto-Kakizaki (GK) type 2 diabetic rats, we observed a significant reduction in ROCK1 activity in the retinal pigment epithelium/choroid complex after 8 days and relocation of ROCK1 to the cytoplasm and nucleus in retinal pigment epithelium cells after 28 days. The chronic ROCK inhibition by the BIRKI depot formulation restored retinal pigment epithelial cell morphology and distribution, favored retinal capillaries dilation, and reduced hypoxia and inner blood barrier leakage observed in the diabetic retina. No functional or morphological negative effects were observed, indicating suitable tolerability of BIRKI after intravitreous injection. In conclusion, our data suggest that sustained ROCK inhibition, provided by BIRKI slow-release formulation, could be a valuable treatment option for diabetic retinopathy, especially with regard to the improvement of retinal vascular infusion and protection of the outer retinal barrier.